1999
DOI: 10.1063/1.123459
|View full text |Cite
|
Sign up to set email alerts
|

A narrow photoluminescence linewidth of 21 meV at 1.35 μm from strain-reduced InAs quantum dots covered by In0.2Ga0.8As grown on GaAs substrates

Abstract: InAs quantum dots with size fluctuations of less than 4% were grown on GaAs using the self-assembling method. By covering the quantum dots with In0.2Ga0.8As or In0.2Al0.8As, strain in InAs dots can be partly reduced due to relaxation of lattice constraint in the growth direction. This results in low-energy emission (about 1.3 μm) from the quantum dots. The photoluminescence linewidth can be reduced to 21 meV at room temperature. This width is completely comparable to the theoretical limit of a band-to-band emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
284
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 597 publications
(290 citation statements)
references
References 14 publications
4
284
1
1
Order By: Relevance
“…The system considered consists of InAs QDs grown on GaAs that are capped with In x Ga (1Àx) As, where the lattice mismatch between the QDs and the capping layer is engineered by tuning the In concentration in the capping layer. 14 The effects on the QDs morphology are studied, and the results obtained from the simulation are compared with cross-sectional Scanning Tunnel Microscopy (X-STM) measurement on QD samples grown by Molecular Beam Epitaxy (MBE). 15 In our KMC model for hetero-epitaxial growth every pair of III-V atoms in the system is modeled with a cube, as shown in Fig.…”
mentioning
confidence: 99%
“…The system considered consists of InAs QDs grown on GaAs that are capped with In x Ga (1Àx) As, where the lattice mismatch between the QDs and the capping layer is engineered by tuning the In concentration in the capping layer. 14 The effects on the QDs morphology are studied, and the results obtained from the simulation are compared with cross-sectional Scanning Tunnel Microscopy (X-STM) measurement on QD samples grown by Molecular Beam Epitaxy (MBE). 15 In our KMC model for hetero-epitaxial growth every pair of III-V atoms in the system is modeled with a cube, as shown in Fig.…”
mentioning
confidence: 99%
“…Specifically, when the QDs are covered by an InGaAs strain-reducing layer (SRL), a red-shift of the emission wavelength is observed, depending on the composition and thickness of the SRL [7,8]. The areal density is not significantly affected by the capping, so that the available gain and the wavelength are effectively decoupled.…”
mentioning
confidence: 97%
“…It has been shown that self-assembled InAs/GaAs quantum dots ͑QDs͒ on GaAs substrates can provide optical gain at 1.3 m. [1][2][3][4] A recently proposed method 5,6 to achieve the 1.3 m wavelength is to embed the QDs in an InGaAs quantum well ͑QW͒. This results in a lower transition energy as compared to GaAs-embedded QDs, presumably due to reduced strain in the QDs, suppression of In segregation from the QDs when covering with InGaAs, and lower barrier potential.…”
Section: ͓S0003-6951͑00͒05123-8͔mentioning
confidence: 99%